2019
DOI: 10.1177/1934578x19845815
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity to Five Cancer Cell Lines of the Respiratory Tract System and Anti-inflammatory Activity of Thai Traditional Remedy

Abstract: A Thai traditional remedy called Benchalokawichian (BLW) consists of 5 plant species, Ficus racemosa, Capparis micracantha, Clerodendrum petasites, Harrisonia perforata, and Tiliacora triandra. It has long been used in Thai traditional medicine to reduce fever in respiratory tract infection, but there is no report on either cytotoxicity against cancer cell lines of the respiratory tract system or anti-inflammatory effect. Thus, the objectives of this research were to investigate the cytotoxic activity of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Our findings strongly suggested that the photoprotective actions of HRF extracts and HSP at concentrations of 30 μg/ml and 10 μg/ml, protected against UVA-induced photoaging of NHDFs. As reported by our previous studies and others, the HRF or Benchalokawichian was demonstrated to exert the antipyretic and anti-inflammatory actions in vivo (Jongchanapong et al, 2018) as well as anti-allergic, antiinflammatory antioxidant, anti-collagenase, and depigmenting actions in vitro (Pluemsamran et al, 2013;Onkoksoong et al, 2018;Juckmeta et al, 2019;Noysang et al, 2019). Furthermore, HSP, a citrus flavonoid, has previously shown the anti-inflammatory responses and antioxidant properties by inducing the Nrf2-antioxidant defense system including the GCL and NQO-1 detoxifying antioxidant signaling as well as providing the protective effects against oxidative damage and carcinogenesis (Parhiz et al, 2015;Roohbakhsh et al, 2015;Ren et al, 2016;Biesemann et al, 2018;Ferreira de Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our findings strongly suggested that the photoprotective actions of HRF extracts and HSP at concentrations of 30 μg/ml and 10 μg/ml, protected against UVA-induced photoaging of NHDFs. As reported by our previous studies and others, the HRF or Benchalokawichian was demonstrated to exert the antipyretic and anti-inflammatory actions in vivo (Jongchanapong et al, 2018) as well as anti-allergic, antiinflammatory antioxidant, anti-collagenase, and depigmenting actions in vitro (Pluemsamran et al, 2013;Onkoksoong et al, 2018;Juckmeta et al, 2019;Noysang et al, 2019). Furthermore, HSP, a citrus flavonoid, has previously shown the anti-inflammatory responses and antioxidant properties by inducing the Nrf2-antioxidant defense system including the GCL and NQO-1 detoxifying antioxidant signaling as well as providing the protective effects against oxidative damage and carcinogenesis (Parhiz et al, 2015;Roohbakhsh et al, 2015;Ren et al, 2016;Biesemann et al, 2018;Ferreira de Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
“…As demonstrated by the chemical profiling of HRF and all five components (the roots of five plants used in preparation of the HRF) using the liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (LC-QTOF-MS), hesperetin (HSP) (or the (2S)-5,7-dihydroxy-2-(3-hydroxy-4-methoxyphenyl)-2,3-dihydrochromen-4-one) was also suggested as a putative bioactive constituent of the HRF (Suebnooch et al, 2018). We and others have reported the beneficial roles of the HRF and their components in protecting against skin disorders possibly due to several pharmacological actions in vitro and in vivo including antiacne (Jantarat et al, 2018), anti-allergic (Juckmeta et al, 2014), anti-inflammatory (Juckmeta et al, 2019), antioxidant and anticollagenase (Pluemsamran et al, 2013), depigmenting (Onkoksoong et al, 2018), and wound healing properties (Mehtaa et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Considering the chemical constituents of the herbal principles in the recipe, the cytotoxically active compounds such as pectolinarigenin and perforatic acid were isolated and their activities against cancer cell lines were also investigated in a recent report. 19 However, the other promising cytotoxic agents have still been explored from the plants, which are the ingredients of the recipe. Lupeol, a cytotoxic compound that was determined as one of the active compounds in C. indicum 9 was selected as an analytical marker herein, in order to examine the content in the recipe and also determine whether it was responsible for the cytotoxic activity against SW620 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…BLW comprises the roots of five medicinal plants, including Clerodendrum petasites, Harrisonia perforata, Tiliacora triandra, Capparis micracantha, and Ficus racemosa (National Drug Committee, 2009). BLW and its herbal components consist of bioactive compounds, including alkaloids, flavonoids, and polyphenols (Brimson, Onlamoon, Tencomnao, & Thitilertdecha, 2019;Juckmeta et al, 2019;Noysang & Pummarin, 2019). Biological activities of BLW and its herbal components include anti-inflammatory, antioxidant, antimutation (Singharachai, Palanuvej, Kiyohara, Yamada, & Ruangrungsi, 2011), and antiproliferative activity against lung cancer cell lines (Juckmeta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…BLW and its herbal components consist of bioactive compounds, including alkaloids, flavonoids, and polyphenols (Brimson, Onlamoon, Tencomnao, & Thitilertdecha, 2019;Juckmeta et al, 2019;Noysang & Pummarin, 2019). Biological activities of BLW and its herbal components include anti-inflammatory, antioxidant, antimutation (Singharachai, Palanuvej, Kiyohara, Yamada, & Ruangrungsi, 2011), and antiproliferative activity against lung cancer cell lines (Juckmeta et al, 2019). However, the antiproliferative and apoptosis-inducing activities of BLW and its herbal components against drug-sensitive and drug-resistant cancer cells are unclear.…”
Section: Introductionmentioning
confidence: 99%